Women negotiating modernity: a gender perspective on fundamentalism in Catholicism and Islam - Madigan, Patricia (Islam and Christian-Muslim relations, 2009)
In the present age, the forces of globalized modernity are impacting upon and shifting the power structures of many aspects of civilizations as we have known them. Many studies of ‘fundamentalism’ have rightly diagnosed it as a reactive movement against the forces of modernity, yet fundamentalism has been little studied from a gender perspective. While many of the struggles outlined in this article are being fought out internally within both the Catholic Church and the Islamic world, at times they spill over into international forums, as occurred at United Nations forums in Cairo (1994) and Beijing (1995). This article explores the impact of fundamentalism on women's lives and their responses to it, with a focus on Catholicism and Islam.